Curative architecture, as a regeneration strategy for a vulnerable population with psychological problems - Pacheco Cabrera, Damar Elena; Vasquez Leiva, Keyli Gianella; Saldaña Fustamante, Eber Hernan (LACCEI, 2024)
The investigation is carried out based on the psychologicalproblems that affect the inhabitants of Ayacucho, diseases that hinderthe daily life of its citizens and the integral development of the city.Based on this, the research work addresses the objective of determiningarchitectural design principles for a Center for the Treatment andprevention of psychological problems based on the principles of StefanLundin's curative architecture in the province of Ayacucho 2023. Themethodology used it is of a non-experimental type through documentaryreview; to be able to carry out, based on this, an architectural study inthe selected environment, making use of different instruments. Theresult of the investigation resulted in both theoretical and technicalguidelines, being applied through different types of enclosures inexterior spaces such as perimeter wall areas and interior spaces such aswaiting rooms, workshops and main entrances, different types of scalessuch as double heights, employment of green areas between thedifferent UPSS to generate visuals and direct connection with theoutside, strategies for an adequate location, integrating the project withthe environment.